Change and immobility in mountain Corfu - Couroucli, Maria (The Greek Review of Social Research, 1981)
This paper is based on a historical anthropological study carried out at Episkepsi, a mountain village in Corfu. Archival material has helped to trace the evolutionof the demographic and economic struc tures of the community for more than two centuries. During the inter-war period the peasant serfs (coloni) became land owners thanks to the agrarian reform, at the same time when modern technology was being introduced in the village economy. This produced a radical change in termsof social relations of production, but the village soon adapted to the new reality while pursuing the traditional economy based upon olive cultivation—which has become the only commer cialised production of the village. Episkepsi is now rather prosperous and has been able to adopt a modern way of life. It has broken its geographic isolation by opening itself to the wider society, but it has also preserved part of its tradi tional structure, thus ensuring the survival of the community as a social unit.